Electro‐Optics: Yellow‐Colored Electro‐Optic Crystals as Intense Terahertz Wave Sources (Adv. Funct. Mater. 30/2018). (23rd July 2018) - Jeong, Chan‐Uk; Kang, Bong Joo; Lee, Seung‐Heon; Lee, Seung‐Chul; Kim, Won Tae; Jazbinsek, Mojca; Yoon, Woojin; Yun, Hoseop; Kim, Dongwook; Rotermund, Fabian; Kwon, O‐Pil
Abstract : In article number1801143, Fabian Rotermund, O‐Pil Kwon, and their co‐workers report yellow‐colored electro‐optic salt crystals possessing large macroscopic optical nonlinearity with wide transparency. The crystals exhibit excellent THz wave generation characteristics. The THz spectral shape is significantly different when compared to red‐ or orange‐colored organic electro‐optic crystals, which are used for most benchmark organic THz sources.